STRES KERJA PADA TENAGA PENJUALAN PRODUK KECANTIKAN CV VITA PERMAI KOTA KUPANG - Regitha A. Beeh; M.K.P Abdi Keraf; Diana Aipipidely; Noorce Ch Berek (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Job stress is a common problem experienced by salespeople due to the demands of achieving targets, high workloads, and dynamic working conditions. This condition has the potential to affect the physical, psychological, and behavioral health of salespeople, thus impacting their performance and well-being. This study aims to describe and analyze the experiences of job stress experienced by salespeople, the factors causing stress, and its impact on daily work activities. The focus of the study is directed at physiological, psychological, and behavioral aspects in response to job stress. This study uses a qualitative approach with a phenomenological method. Data collection was conducted through in-depth interviews with purposively selected informants, accompanied by observation and documentation as supporting data. The data analysis process was carried out through the stages of data reduction, data presentation, and drawing conclusions to obtain a comprehensive understanding of the phenomenon under study. The research results show that work stress causes physical impacts such as fatigue, body aches, and minor health problems; psychological impacts such as anxiety, emotional instability, and decreased work motivation; and behavioral impacts seen in decreased concentration and work effectiveness. The main factors causing stress include pressure from sales targets, excessive workload, and limited rest time. The study's conclusions confirm that work stress in salespeople is multidimensional and requires organizational attention through workload management, adequate work support, and strategies to improve employee well-being.